2013
DOI: 10.1016/j.jvs.2013.02.252
|View full text |Cite
|
Sign up to set email alerts
|

Current efficacy of open and endovascular interventions for advanced superficial femoral artery occlusive disease

Abstract: There has been a marked shift in treatment modality for advanced femoro-popliteal disease with a lowering of the symptomatic threshold for intervention over 2 decades, likely spurred by the ease of endoluminal interventions. Although peri-procedural and anatomic outcomes for both procedures are equivalent, it appears that open surgery carries a superior long-term clinical efficacy. This superiority is negatively influenced by poor preoperative ambulation status, high modified Cardiac Risk Score, worse presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…The present study demonstrated superior objective performance goals for MALE and AFS 9 and comparable primary, assisted primary, and secondary patency and limb salvage rates, in keeping with our published reports on antegrade femoral interventions. 2 CE was high and freedom from MALE and AFS were high, reflecting the fact that most of the patients presented with claudication. These data suggest that comparable longer term outcomes can be achieved when the retrograde approach is used.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study demonstrated superior objective performance goals for MALE and AFS 9 and comparable primary, assisted primary, and secondary patency and limb salvage rates, in keeping with our published reports on antegrade femoral interventions. 2 CE was high and freedom from MALE and AFS were high, reflecting the fact that most of the patients presented with claudication. These data suggest that comparable longer term outcomes can be achieved when the retrograde approach is used.…”
Section: Discussionmentioning
confidence: 99%
“…Definitions of all outcome parameters have been described elsewhere. 2 Analyses were performed using JMP software version 9.0 (SAS Institute, Cary, NC).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations